(untitled) (TEL Tempo, Espaço e Linguagem, 2019)
Translation into Portuguese of “La loi du genre”, by Jacques Derrida. Text presented in July 1979 as an oral communication in a colloquium on gender held at the University of Strasbourg. Derrida reflects on gender in literature, as a literary mode, from Gérard Genette, as well as as a question of masculine and feminine and its relation to a law. The basis of analysis will be La folie du jour, by Maurice Blanchot who, despite being narrative, resists a definitive classification.